Optimization of cooling parameters of forming roll of the battery greed continuous casting machine - E. F. Baranovsky; V. M. Iljushenko; V. A. Pumpur; A. I. Kalentionok (Литьë и металлургия)
The mathematical description of heat exchange in a roll of the mould for battery greed continuous casting is proposed. The roll’s cooling parameters minimizing non-uniformity of its profile are determined.